1292 Aortic Valve Neocuspidization Using Glutaraldehyde-Treated Autologous Pericardium: A Literature Review. (12th October 2021) - Chan, J; Basu, A; Discenza, G; Bartlett, J; Fan, K S; Oo, S
Abstract: Background: Aortic Valve Neocuspidization using glutaraldehyde-treated autologous pericardium was first performed by Ozaki et al. in 2007. This technique has become an alternative to tissue and mechanical valve as long-term anticoagulation is not required and shows promising midterm results and durability. Method: A comprehensive search was performed on the major database using search terms "Ozaki technique" AND "Aortic Valve Neocuspidization" AND "AV Neocuspidization" AND "Autologous pericardium" AND "glutaraldehyde-treated autologous pericardium". Articles up to 1 st of August 2020 were included in this study. Results: A total of 9 studies with a total of 1342 patients were included. The mean age was 67.36 and 54.23% were male. 66.32% and 23.92% of patients had aortic stenosis and aortic regurgitation, respectively. 66% of patients had a native tricuspid aortic valve and 31.37 % patients' native aortic valve was bicuspid. Three studies reported their experience performing Aortic Valve Neocuspidization via mini sternotomy. Conclusions: Aortic Valve Neocuspidization is an alternative to biological and mechanical prostheses for surgical aortic valve replacement. The short and mid-term outcome are comparable without the need for long term oral anticoagulation. Long term follow-up data is required for this novel approach to be widely adopted.